2013
DOI: 10.1590/s1413-78522013000100011
|View full text |Cite
|
Sign up to set email alerts
|

Estimulação elétrica neuromuscular na disfunção patelofemoral: revisão de literatura

Abstract: Patellofemoral dysfunction is a fairly common deficiency among young individuals that primarily affects females and may be characterized by pain, swelling and retropatellar crepitation. The purpose of this review of literature from the period between 2005 and 2011 was to systematize knowledge in relation to the increase in quadriceps muscle strength and pain relief in patients with patellofemoral dysfunction, using neuromuscular electrical stimulation and resistance exercises. The inclusion criteria were inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 18 publications
(28 reference statements)
1
5
0
Order By: Relevance
“…The mean force of the quadriceps both in the affected limb and in the contralateral limb showed a significant gain (p < 0.001 for both). These results are supported by previously published data 5 , 6 claiming that when a decrease in symptoms of pain in the treated region occurs, a gain in strength can be achieved. Since the volunteers perceived a reduction in previously experienced pain, they were able to train properly again, as pain is a limiting factor for muscle function.…”
Section: Discussionsupporting
confidence: 88%
“…The mean force of the quadriceps both in the affected limb and in the contralateral limb showed a significant gain (p < 0.001 for both). These results are supported by previously published data 5 , 6 claiming that when a decrease in symptoms of pain in the treated region occurs, a gain in strength can be achieved. Since the volunteers perceived a reduction in previously experienced pain, they were able to train properly again, as pain is a limiting factor for muscle function.…”
Section: Discussionsupporting
confidence: 88%
“…In addition to muscular strengthening, neuromuscular electrical stimulation (NMES) is an effective strengthening modality following knee injuries 82-86 . NMES minimizes atrophy associated with immobilization in terms of both thigh muscle size and mass 84,85 .…”
Section: Nonoperative Rehabilitationmentioning
confidence: 99%
“…Systematic reviews and RCTs have demonstrated a lack of supportive evidence for the use of physical agents such as therapeutic ultrasound, phonophoresis, iontophoresis, transcutaneous electrical nerve stimulation, medium-frequency neuromuscular electrical stimulation, low-level laser, extracorporeal shock-wave therapy, electromyographic biofeedback and massage therapies. 102 , 125 , 151 , 152 There is little justification for using these modalities alone for PFP patients. 102 , 126 However, despite the lack of clear evidence currently, cryotherapy is still recommended as a part of the conservative treatment for PFP.…”
Section: Managementmentioning
confidence: 99%